A note on the glacial geology and postglacial emergence of the Lake Harbour region, Baffin Island, N.W.T. - Clark, Peter (Canadian Journal of Earth Sciences, 1985)
Ice-flow indicators in the Lake Harbour region of northern Hudson Strait define two flow directions affecting this area during the late Wisconsinan glaciation. A pronounced southward flow direction indicated by medium- and large-scale erosional and depositional features represents ice flow from an ice dome centered to the north, perhaps Foxe Basin and (or) Amadjuak Lake. Carbonate-rich till and striations represent eastward–southeastward ice flow down the axis of Hudson Strait. Convergence of ice-sheet flow with a rapidly moving ice stream has been observed and modelled for West Antarctic ice streams and involves sharp bending of flow lines at the point of convergence. A similar scenario is proposed for the Lake Harbour region to explain the two contrasting ice-flow patterns. Impingement of an ice stream in Hudson Strait onto the southern coast of Baffin Island suggests the influence of northerly flowing ice, perhaps from the Ungava plateau.Radiocarbon dates on marine shells and archeological samples are used to reconstruct the postglacial emergence of the Lake Harbour region. The marine limit (90 m aht) and deglaciation are dated by extrapolation at ca. 8300 years BP. Postglacial emergence is characterized by an initial uplift rate of 4.4 m/100 years, which decreased to 0.2 m/100 years over the last 3900 years. The initial rate (4.4 m/100 years) is nearly 50% lower than rates calculated elsewhere in the Hudson Strait region and is interpreted to reflect the influence of an ice load centered over Amadjuak Lake directly north of the Lake Harbour region.